2022
DOI: 10.1097/fjc.0000000000001290
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Mitochondrial Respiration During Early Reperfusion Reduces Cardiac Injury in Donation After Circulatory Death Hearts

Abstract: :Donation after circulatory death (DCD) donors are a potential source for heart transplantation. The DCD process has unavoidable ischemia and reperfusion (I/R) injury, primarily mediated through mitochondria, which limits routine utilization of hearts for transplantation. Amobarbital (AMO), a transient inhibitor of the electron transport chain, is known to decrease cardiac injury following ex vivo I/R. We studied whether AMO treatment during reperfusion can decrease injury in DCD hearts. Sprague Dawley rat hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Mitochondria ETC plays a vital role in oxidative stress under either physiological or pathological conditions [32]. Since numerous experiments have demonstrated that blocking the ETC can reduce the oxidative stress injury of myocardial cells [18], such as amobarbital [16,33]. In our study, fow cytometry analysis suggested that the reduction of Ndufs4 subunit expression can decrease the H9c2 apoptosis ratio from 40% to 18%, and mitigate H9c2 injury.…”
Section: Discussionmentioning
confidence: 51%
“…Mitochondria ETC plays a vital role in oxidative stress under either physiological or pathological conditions [32]. Since numerous experiments have demonstrated that blocking the ETC can reduce the oxidative stress injury of myocardial cells [18], such as amobarbital [16,33]. In our study, fow cytometry analysis suggested that the reduction of Ndufs4 subunit expression can decrease the H9c2 apoptosis ratio from 40% to 18%, and mitigate H9c2 injury.…”
Section: Discussionmentioning
confidence: 51%
“…Inhibition of this process with malonate is cardioprotective and would also be expected to improve cardiac recovery following DCD [112]. Indeed, in a rat model of DCD, the transient inhibition of mitochondrial complex I during early reperfusion led to reduced cardiac injury, likely due to decreased ROS production [113]. Also, an inhibitor of reverse electron transport (RET), which is a key mechanism for mitochondrial ROS production during reperfusion, could be used [111], or indeed, ROS scavengers.…”
Section: Potential Metabolic-based Cardioprotective (Reperfusion) Str...mentioning
confidence: 99%
“…6 In an ex vivo ischemia-reperfusion model, when AMO was administered during early reperfusion, it decreased cardiac injury in DCD hearts. 7 The beneficial effects of AMO in in vivo ischemia-reperfusion settings were not studied; hence, we elected to study the contribution of AMO treatment during reperfusion to improve function in transplanted DCD hearts when added to a standard cardioplegic solution.…”
Section: Introductionmentioning
confidence: 99%